Planning for the Construction of Facilities and Infrastructure for Household Waste Management in Parung Panjang District - Maulana, Muhammad Afif; Heryansyah, Arien (Universitas Ibn Khaldun, 2023)
(1) Careless disposal of household waste around the house or to the street has become a habit of some people in Parung Panjang District, Bogor Regency, causing several environmentally based diseases and polluting the environment. Therefore, it is necessary to conduct a (3) study on household waste management based on technical, operational, institutional, financing, legal/regulatory aspects and community participation. (4) This observation aims to examine household waste management and correlated factors, as well as plan community-based household waste management. (5) The suggestions given include: To make a better environment, facilities and infrastructure must be adequate, there must be TPSS for disposal facilities, to maximize the improvement of waste management services by the HSS District Government, in this case the Environment, Urban and Rural Planning, then prepare technical aspects of operations, strict enforcement of local laws/regulations, and involve private parties and the Journal of Environmental Sciences in the aspect of its financing. Improving waste services, establishing village waste management groups, involving the public and private sector in financing, increasing cross-sectoral coordination and involving community and religious leaders, as well as strict implementation of waste regulations.